Exploring the Relationship between Hygiene Factors and Job Satisfaction in Workplace - Mahmood, Nor Asiah; Tajuddin, Nur Ilyana Ismarau (Journal of Ecohumanism, 2024)
The purpose of this research is to investigate the relationship that exists between hygiene factors and job satisfaction (JS) among the Royal Malaysian Navy (RMN) personnel in the workplace. The focus shall be directed toward the diligent personnel on board at Lumut Naval Base. The present study adopts a quantitative analysis methodology, employing a straightforward descriptive approach and correlation analysis through SPSS 23, wherein a sample of 220 employees was randomly selected for analysis. The empirical evidence suggests that there exist notable associations between job satisfaction (JS) and various factors, namely company policy, salary and benefits, and interpersonal relationships. The variables of job security and working conditions do not exhibit a statistically significant correlation with job satisfaction. The findings of this study suggest that there exists a noteworthy correlation between variables towards Job Satisfaction (JS). Therefore, there is no significant correlation between Job Security and Working Conditions in JS. The study's impact extends beyond the organization, encompassing the broader field, as it adds to the body of literature about the research elements. The utilization of models and theoretical frameworks in prospective investigations presents a distinct point for comprehending and interpreting phenomena that represents a noteworthy innovation within the context study.